The impact of long-acting Gonadotropin-releasing hormone agonist pretreatment on the clinical pregnancy outcomes of hormone replacement therapy-frozen embryo transfer in recurrent implantation failure patients with and without polycystic ovary syndrome: a retrospective clinical study - Chenyang Huang; Yuan Yan; Jie Mei; Yue Jiang; Haixiang Sun; Jun Xing (BMC Pregnancy and Childbirth)
Abstract Background Several studies have demonstrated that pre-treatment with long-acting Gonadotropin-Releasing Hormone agonists (GnRHa) can significantly enhance the clinical pregnancy rate among recurrent implantation failure (RIF) patients. Investigations have also suggested that GnRHa pre-treatment could ameliorate the clinical pregnancy and live birth rates in polycystic ovary syndrome (PCOS) patients. But there is a dearth of research on whether long-acting GnRHa pre-treatment yields superior clinical outcomes for RIF patients with PCOS. Methods The retrospective study enrolled 1602 patients under the age of 40 meeting the criteria for RIF at the Reproductive Medicine Center of Nanjing Drum Tower Hospital, who underwent frozen-thawed embryo transfer (FET) between January 2017 and December 2021. All cycles were categorized into hormone replacement therapy (HRT) Group (n = 1283) and GnRHa-HRT Group (n = 319), contingent on the usage of long-acting GnRHa pretreatment. Primary outcomes investigated in this study was clinical pregnancy rate, while live birth rate and early miscarriage rate were deemed as secondary outcomes. Univariate analysis and a multivariate logistic regression model were employed to assess the impact of GnRHa pretreatment on the clinical pregnancy rate in RIF patients. The influence of long-acting GnRHa pretreatment on clinical pregnancy outcomes was re-examined in PCOS and non-PCOS subgroups. Additionally, an interaction analysis was performed to evaluate the effect of PCOS on the relationship between long-acting GnRHa pretreatment and the clinical pregnancy rate. Results Multiple regression analysis showed that long-acting GnRHa pretreatment had a positive impact on the clinical pregnancy rate (aOR = 1.51, 95%CI: 1.15–1.99, P = 0.003). We divided the RIF population into two subgroups, for PCOS patients, although the clinical pregnancy rate was higher in women who received GnRHa pretreatment compared to those who did not, it was not statistically significant (aOR = 1.51, 95%CI: 0.81–2.82, P = 0.195). Interaction analysis suggested that for PCOS patients, there was no significant difference in the clinical pregnancy rate between women who received GnRHa pretreatment and those who did not (P interaction = 0.818), indicating that the effect of GnRHa pretreatment on the clinical pregnancy rate was not influenced by PCOS. Conclusions Our study demonstrates that long-acting GnRHa pretreatment can enhance clinical pregnancy outcomes in patients with RIF. Among RIF patients without PCOS, the clinical pregnancy rate exhibited a significant increase following GnRHa pretreatment compared to the control group. However, in RIF patients with concurrent PCOS, there was no significant elevation in the clinical pregnancy rate post-GnRHa pretreatment. Therefore, GnRHa pretreatment is effective in improving pregnancy outcomes for RIF patients. However, whether GnRHa pretreatment is suitable for RIF patients with PCOS requires more cautious clinical discussion.